Pengaruh pendidikan islam terhadap masyarakat - Muzaki, Miftakhul (Maliki Interdisciplinary Journal, 2024)
Education is an important aspect in people’s lives, because education can shape a person’s behavior and character in behaving and ethically in everyday life. Not only does it shape character, education also has an important role in human success in the future. In this era of society, it is felt necessary to instill Islamic education in society. Basic Islamic education is usually implemented in the family environment, where the role of parents is very important. Of course, parents want their children’s education to be much better and able to understand their religion, so it’s no wonder parents are looking for the best education by looking at the curriculum being taught. The role of education is also as a foundation in the family to shape children’s behavior in limiting good and bad things, as well as playing a role in moral education for the development of Indonesian society. The purpose of writing this research is to find out how important Islamic education is in people’s lives, not only for children but also for all groups because Islamic education is the basis for everyday life, because the process of Islamic education has two points of view in several aspects, such as external and internal aspects. The method used in this research uses the literature review method, namely a method that uses library data collection, reading and taking notes, and managing the research data to be studied.